Excited‐state intramolecular proton transfer of 6‐amino‐2‐(2′‐hydroxyphenyl) benzoxazole (6A‐HBO) in different solvents. (14th October 2018) - Du, Can; Zhou, Qiao; Zhang, Meixia; Song, Peng; Ma, Fengcai
Abstract: The excited‐state intramolecular proton transfer (ESIPT) process of 6‐amino‐2‐(2′‐hydroxyphenyl) benzoxazole (6A‐HBO) was investigated using density functional theory and time‐dependent density functional theory methods with B3LYP and TZVP basis sets. n ‐Heptane, dichloromethane, methanol, and acetonitrile were chosen as a series of polar solvents in calculations using the IEFPCM model. To obtain a more comprehensive ESIPT mechanism, we constructed the S0 and S1 states' potential energy surfaces (PESs) by incrementally twisting the ─OH bond and increasing the distance of O–H bond. Based on the analysis of the bond lengths, the IR vibrational spectra, and the frontier molecular orbits (MOs), the intramolecular hydrogen bonding (O─H...N) is clearly strengthened, and the charge is redistributed in the S1 state. The results of calculated absorption spectrum are in accord with the experimental data. The fluorescence spectrum of 6A‐HBO‐enol showed a normal red shift, but the red shift of the 6A‐HBO‐keto is larger and increases with the solvent polarity, indicating a charge transfer. Analysis of the PESs indicates a lower potential energy barrier in S1 state for the proton transfer from the O atom to the N atom, with the excited state potential barrier slightly decreasing with the increase of the solvent polarity. Abstract : The intramolecular hydrogen bond of 6A‐HBO is strengthened in the S1 state. The hydrogen bonding (O─HN) can promote the ESIPT reaction of 6A‐HBO. The ESIPT only happens in the S1 state with the proton transfer from O atom to N atom.